Direct and Semi-direct effects of aerosols in West Africa during the dry season - (:unkn) unknown (My University, 2011)
This work investigates direct and semi-direct aerosol radiative forcing and the associated climatic impacts over the West African region during the dry-season. The regional climate model version 3 (RegCM3) is used in combination with in-situ observations from the AMMA-SOP0/DABEX field campaigns and remote sensing observations from sunphotometry (AERONET/PHOTON) and satellite platforms (PARASOL, MODIS, OMI and MISR). RegCM3 is specifically configured to represent West African aerosols and is evaluated for the 2006 dry season. In this setup, RegCM3 is found to represent aerosol loadings accurately enough for climatic applications, with the model simulating consistent aerosol single scattering albedo variations. In December and January, when smoke aerosols dominate the background aerosol loading, the aerosol single scattering albedo over the Sahel ranges from 0.81to 0.83 (at 440 nm). During the months of March and April, when dust aerosol are mainly observed, the simulated aerosol single scattering albedo ranges between 0.90 and 0.92 (at 440 nm). The direct aerosol radiative forcing (visible + infrared) estimated at top of the atmosphere is essentially negative over the whole domain, with values ranging from -5 W/m² to -4.0 W/m². Over the Sahara, the direct aerosol radiative forcing at top of the atmosphere (TOA) is close to zero (-0.15 W/m²). The large difference between the TOA and surface direct radiative forcing indicates strong radiative absorption in the atmosphere (+11.47 and +24.40 W/m² over the Sahara and Sahel, respectively). Due to their relatively low single scattering albedo, smoke aerosols are the dominant contributors to atmospheric heating. At the regional scale, this results in a daily average atmospheric heating rates ranging between +0.2 and +0.6 K/day within the main smoke layers (approximately 2 and 5 km above the ground surface). Two longer simulations covering the 2001-2006 period are also conducted in order to investigate the e
Keywords: African Research